Detection of Ferulic Acid in Maize Plant under Drought Stress Using an RP-HPLC Method - Rai, Piyush Kant; Choure, Kamlesh (International Journal of Economic Plants, 2024)
The experiment was conducted from April to May 2024 at the Centre for Excellence in Biotechnology in Research and Training (CEBRT) lab of Amicable Knowledge Solution University (AKS) University, Satna. In the present study, a simple, routine, and reproducible RP-HPLC method was employed for estimating the levels of Ferulic acid (FA) in different treatments of maize that is essential in the phytochemical analysis of this plant, has been assessed based on ferulic acid (FA). The method used in this study was based on HPLC on a C18 column using a gradient of water, methanol, and acetic acid. The calibration curve showed optimum linearity from 10 to 100 µg ml-1, with R²=0.981. This method is used to quantify the concentration, of FA. This methodology was used to detect FA in maize plants with different treatments: T1: control plants, T2: drought-induced plants, T3: plants inoculated with PKR1, T4: plants inoculated with PKR5, T5: plants inoculated with PKR6. The increase in FA was observed in all three Plant Growth Promoting Rhizobacteria (PGPR)-treated plants (T3, T4, and T5) as compared to T1: control plant and T2: drought-induced plants. Among these, maximum FA was found in T4 treatment, and the maximum peak height and area of T4 were 229259 and 10884, respectively. The Reverse-phase high-performance liquid chromatography (RP-HPLC) RP-HPLC analytical methodology was validated for reliable analysis of FA content in maize leaves, contributing to phytochemical studies and quality assurance in different plant treatments and their derived products.